ATLANTIS IN SPAIN I - Papamarinopoulos, S.P (Bulletin of the Geological Society of Greece, 2010)
Dealing with Plato’s Atlantis one should be aware that its author is the very first person in the world who defined science’s and mythology’s concepts. However, he introduced several times paramyths in his dialogues and he encrypted in them moral, philosophical, political, mathematical, musicological information and other ideas. Such a person wrote the famous Atlantis story. We shall attempt desipher fully in the successive texts but before we do that we need to familiarize the reader in order to understand the breaking of a 2400 years complexity which will be presented through the Hellenic Geological Society’s 12th International Symposium organized by the Patras University Department of Geology.